2017
DOI: 10.22146/jps.v4i2.28586
|View full text |Cite
|
Sign up to set email alerts
|

Mengembangkan Model Literasi Media yang Berkebhinnekaan dalam Menganalisis Informasi Berita Palsu (Hoax) di Media Sosial

Abstract: AbstraksiUjaran kebencian (hate speech) mengiringi kebebasan berpendapat di media sosial. Sejak pilpres 2014 lalu, istilah 'hater' pun dikenal luas, yang menandai orang-orang dengan kecenderungan membuat pesan ujaran kebencian pada orang atau kelompok tertentu. Kebhinnekaan sebagai pengikat sosial diuji karena kecenderungan praktik ujaran kebencian yang dipromosikan melalui media sosial. Kondisi itu diperparah oleh penyalahgunaan media sosial seperti persebaran berita bohong atau informasi palsu (hoax) yang da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
44

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 0 publications
0
26
0
44
Order By: Relevance
“…Through social media, hundreds or even thousands of information are distributed every day. Even people sometimes do not have time to understand information material, the reaction to that information has already been seen ( Juliswara, 2017) In qualitative research there are general characteristics; has a natural setting as the data source is direct, the researcher as the main instrument, is descriptive, qualitative researchers are more concerned the process then with the results (outcomes or products), the data are analyzed inductively and meaning is very important.…”
Section: Hoax Mediamentioning
confidence: 99%
“…Through social media, hundreds or even thousands of information are distributed every day. Even people sometimes do not have time to understand information material, the reaction to that information has already been seen ( Juliswara, 2017) In qualitative research there are general characteristics; has a natural setting as the data source is direct, the researcher as the main instrument, is descriptive, qualitative researchers are more concerned the process then with the results (outcomes or products), the data are analyzed inductively and meaning is very important.…”
Section: Hoax Mediamentioning
confidence: 99%
“…Mereka merasa sah-sah saja untuk menggunggah tulisan, gambar atau video apapun ke dalam akunnya. Meskipun terkadang mereka tidak sadar bahwa apa yang mereka unggah tersebut bisa saja melanggar etika berkomunikasi dalam media sosial (Juliswara, 2017). Demikian pula halnya dengan Ibu-ibu rumah tangga ternyata banyak mendapatkan Informasi hoax, seperti berita-berita, iklan -iklan, hadiah-hadiah, dan penipuan.…”
Section: Dewi Noviantiunclassified
“…Even the low level of information literacy is the cause of the spread of hoax news [15], [16]. So that the ability of information literacy in the media becomes a relevant need to be immediately carried out to develop the empowerment of netizens in responding to the spread of hate messages in the online realm, especially through social media [17]. Other research also found that there was an effective increase in the academic scores of students after they were given an information literacy strengthening program [18].…”
Section: Basic Ontology Information Literacymentioning
confidence: 99%